Solidarność Walcząca . biuletyn Międzyzakładowego Komitetu "S" Ziemi Łódzkiej, no. 79, 1987 - Krasicki, Ignacy; Słodkowski, Wojciech; Dłużniewski, Jerzy; Lipski, Paweł; Niedbała, Andrzej (MKS NSZZ "Solidarność"], 1987)
Print run: 3000+60-7000 copies